Penerapan business model canvas sebagai alternatif strategi bisnis pada UKM Rumah Karawo - Prabowo, Dimas Aryanto; Wolok, Eduart; Junus, Stella (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop competitive strategies for Rumah Karawo, a prominent SME in Gorontalo, using the Business Model Canvas (BMC) framework. Employing a qualitative descriptive approach, data were gathered through interviews, observations, and documentation. The research analyzes nine key elements of BMC: Customer Segments, Value Propositions, Channels, Customer Relationship, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure, SWOT analysis was also integrated to identify internal strengths and weaknesses as well as external opportunities and threats. The findings highlight that Rumah Karawo’s distinct value propositions, including innovative designs and cultural motifs, serve as strengths, while limited market reach presents challenges. Strategic recommendations include diversifying distribution channels and leveraging digital platforms to enhance market penetration. This study contributes to the visualization of BMC in fostering sustainable competitive advantages for SMEs.